FULFILLMENT OF WOMEN'S AND CHILDREN'S RIGHTS IN THE IMPLEMENTATION OF HUMAN RIGHTS CARE CITIES IN THE CITY OF TERNATE - Limatahu, Muhaimin; Fathurrahim, Fathurrahim; Umra, Sri Indriyani (Khairun Law Journal, 2022)
Efforts to develop cities that care about human rights are a growing response from the movement to restore city sovereignty to its citizens. The state, including the government, supported by the National Human Rights Commission, is trying to apply this idea in Indonesia. The role of local government is very important in supporting efforts to develop cities that care about human rights. Of these problems, the focus of the research is whether the fulfillment of the rights of women and children in Ternate City meets the criteria of a city that cares about human rights and what is the role of the Government of Ternate City in fulfilling the rights of women and children in Ternate City. The human rights movement in Indonesia has begun to launch a new discourse, cities concerned with human rights (human rights cities). One of the interests in studying this issue is to widen the scope of state obligations that are not solely borne by the central government, but also local or regional governments. It is in this context that the role and position of regional leaders is very important. They have the discretion to organize and manage the city government as well as mobilize and invite city residents to be involved in human resource development programs through cities that care about human rights.